Unraveling the Metabolic Derangements Occurring in Non-infarcted Areas of Pig Hearts With Chronic Heart Failure - Correia, Cláudia; Wang, Qing-Dong; Linhardt, Gunilla; Carlsson, Leif G.; Ulfenborg, Benjamin; Walentinsson, Anna; Rydén-Markinhutha, Katarina; Behrendt, Margareta; Wikström, Johannes; Sartipy, Peter; Jennbacken, Karin; Synnergren, Jane (Frontiers in Cardiovascular Medicine, 2021)
Objective: After myocardial infarction (MI), the non-infarcted left ventricle (LV) ensures appropriate contractile function of the heart. Metabolic disturbance in this region greatly exacerbates post-MI heart failure (HF) pathology. This study aimed to provide a comprehensive understanding of the metabolic derangements occurring in the non-infarcted LV that could trigger cardiovascular deterioration. Methods and results: We used a pig model that progressed into chronic HF over three months following MI induction. Integrated gene and metabolite signatures revealed region-specific perturbations in amino acid- and lipid metabolism, insulin signalling and, oxidative stress response. Remote LV, in particular, showed impaired glutamine and arginine metabolism, altered synthesis of lipids, glucose metabolism disorder and increased insulin resistance. LPIN1, PPP1R3C, PTPN1, CREM and NR0B2 were identified as the main effectors in metabolism dysregulation in the remote zone and were found differentially expressed also in the myocardium of patients with ischemic and/or dilated cardiomyopathy. In addition, a simultaneous significant decrease in arginine levels and altered PRCP, PTPN1 and ARF6 expression suggest alterations in vascular function in remote area. Conclusions: This study unravels an array of dysregulated genes and metabolites putatively involved in maladaptive metabolic and vascular remodelling in the non-infarcted myocardium and may contribute to the development of more precise therapies to mitigate progression of chronic HF post-MI.